PENGARUH LATIHAN SENAM LANTAI TERHADAP HASIL KESEIMBANGAN (BALANCE) STATIS SISWA - Heri Afdhal Nurhakim; Andika Triansyah (Fakultas Ilmu Keolahragaan UM)
Abstract: Problems in penelititan are students who are less able to hold the balance with a long time in the gymnastics floor exercise due to lack of time to move or get used to heighten the feeling of motion / movement boundaries. The purpose of the study to determine the effect on the result gymnastics floor equilibrium (balance) in the tenth grade male student School SMA Negeri 4 Singkawang. The research method is experiment with the form of pre-experimental design. The study population was male student of class X School SMA Negeri 4 Singkawang amounted to 57 orang.Teknik sampling is random sampling with a sample size of 20 people. The data analysis using t-test. The results of data analysis ttest = 7,988, with table = 2,093. Value of ttest = 7,988 greater than the value table = 2,093. Based on these results, we can conclude that there are significant floor exercises on the results of equilibrium (balance) static on male students of class X School SMA Negeri 4 Singkawang.Keywords: Gymnastics Floor Exercise, Balance, Static.